2020
DOI: 10.1186/s12884-020-03386-w
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge deficit on health promotion activities during pregnancy: the case for adolescent pregnant women at Chiladzulu District, Malawi

Abstract: Background Adolescent pregnancy is a public health concern in Malawi as it is associated with high risks of adverse pregnancy outcomes. Almost 29% of adolescent women aged 15–19 years are already mothers and adolescent fertility rate is also high estimated at 136 per 1000 women. Therefore, the aim of the study was to explore knowledge of pregnant adolescents on importance of antenatal care and health promotion during pregnancy. Methods A qualitative descriptive design was used to solicit information on signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, multiple studies have found that pregnant women struggle to understand health information (32)(33)(34)(35). In our study, participants struggled to align their behaviour with their health knowledge and lacked support from health professionals.…”
Section: Discussionmentioning
confidence: 84%
“…However, multiple studies have found that pregnant women struggle to understand health information (32)(33)(34)(35). In our study, participants struggled to align their behaviour with their health knowledge and lacked support from health professionals.…”
Section: Discussionmentioning
confidence: 84%
“…This may mean that women do not know what to expect from health care providers or their expectations on the care to be provided is low. Therefore, women need to be well informed about the services they should expect from health care providers and be able to ask for it if not provided [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The participants expressed a lack of knowledge regarding pregnancy-related sickness, delivery process, and dietary needs as well as taking care of the newly born child. A recent study among adolescent pregnant women has shown knowledge deficit on the benefits of ANC and nutrition during pregnancy, that may contribute to poor pregnancy outcomes [ 47 ].…”
Section: Discussionmentioning
confidence: 99%